PENERAPAN PEMBELAJARAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN BIOLOGI DI KELAS XI SMA PGRI PEKANBARU TAHUN AJARAN 2015/2016 - Rizwini Apriani; Evi Suryawati; Arnentis ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study aims to determine students' critical thinking skills improvement through the application of the model Problem Based Learning (PBL) in biology learning in class XI SMA PGRI Pekanbaru. This research was conducted in class XI SMA PGRI Pekanbaru MIA 3 TA second semester 2015/2016. When the study from April to May 2016. The subjects in this study were students of class XI MIA 3 FY 2015/2016 with 23 students. The instrument used in this study is the syllabus, lesson plans and Student Assignment Sheet. The data collection technique were taken from an assessment from of students’ critical thinking skills observation and students attitudes and achievement . The results obtained from this study is the percentage of critical thinking skills of students in the first cycle of 79.7% with prediket B and category Good, increased in the second cycle amounted to 93.1% with prediket A- and category of Very Good. Absorptive capacity in the first cycle to obtain a value of 85.08 prediket B + and Good category, increased in the second cycle of 87.8% with prediket B + and Good category. The completeness of students in the first cycle of 65.21 with prediket Both B- and categories, increased in the second cycle of 82.60 with prediket B + and Good category. While the attitudes of the students earned an average score on the first cycle of 89.1% with prediket B + and Good category, increased in the second cycle of 98.1% with prediket A and category of Very Good. It can be concluded that the adoption of problem based learning (PBL) can provide a positive impact on students' critical thinking skills in school SMA PGRI pekanbaru the academic year 2015/2016.Key Words : Problem based learning, critical thinking skills, Biology